Examining the role of sex on the benefits of muscle‐strengthening activities for people living with obesity: A cross‐sectional study. Issue 4 (4th July 2022) - Keshavarz, Mohammad; Sénéchal, Martin; Dombrowski, Stephan U.; Meister, Daniel; Bouchard, Danielle R.
Abstract: Aims: To investigate the correlations between meeting the muscle‐strengthening activities guideline, body fat %, and mortality for individuals living with obesity and to explore if these correlations are moderated by sex. Methods: Data from 3915 adults ‎(51.9% women; 48.1% men‎) living with obesity (body fat % ≥25 for men and ≥35 for women) from two cycles of the National Health and Nutrition Examination Survey (NHANES 2003‐04/2005‐06) were analyzed. Muscle‐strengthening activities were self‐reported via a questionnaire, body fat % was measured via Dual Energy X‐ray, and mortality was obtained via administrative data for an average of 10 years. Results: 18.7% of men and 15.2% of women living with obesity met the muscle‐strengthening activities guideline ( p = 0.021)‎. Sex was correlated with body fat %; ( β (SE)= 11.34 (0.18); p ≤ 0.001) and risk of mortality (hazard ratio (95% confidence interval) = 0.36 (0.24–0.54); p ≤ 0.001), once adjusted for confounders (weekly aerobic activities, ethnicity, education, household income, smoking, and the sum of chronic conditions). The interaction between sex and meeting the muscle‐strengthening activities guideline was not significantly correlated with the studied outcomes. Conclusion: Performing muscle‐strengthening activities a minimum of two times per week does not impact body fat % or risk of mortality (over 10 years) differently in men or women living with obesity.